Lateral load resisting behavior of steel moment frames with reduced web section (RWS) beams. (December 2020) - Erfani, Saeed; Akrami, Vahid; Mohammad-nejad, Arash
Abstract: Many studies have been conducted on the monotonic and cyclic behavior of beams with Reduced Web Section (RWS) moment connections. However, the use of these structural elements in Steel Moment Resisting Frames (SMRF) have not been much considered. This paper presents a numerical investigation on the lateral load carrying behavior of steel moment resisting frames with reduced web beam sections. For this purpose six multi-story multi-bay structures with different seismic design category, framing type and geometric configurations are designed and modeled numerically. A design procedure for calculating the proper size of opening in the beam web is presented. Then, nonlinear static analysis is conducted on the frames with reduced web beam sections and results are compared with the ones corresponding to the conventional moment resisting frames. Based on the results, the average reduction in initial stiffness and ultimate base shear of the models with perforated beams are 2.5–8.5% and 3.5–6%, respectively. This is while the investigation of yielded areas in these models showed that the plastic zone moved from beam-column connection zones to the openings which is consistent with "Strong column-weak beam" rule. Therefore, the proposed design algorithm can be considered as an effective way to select the proper perforation size which decreases demand for plastic deformation at beam-column connections without causing further decrease in stiffness and strength of the frame.